Kinerja Keuangan Dan Tingkat Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah Di Indonesia - Umiyati Umiyati; Shella Muthya Syarif (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2016)
This research aims to analyze the effect of Return On Asset (ROA), Capital Adequacy Ratio (CAR) and BOPO to the level of profit sharing mudharaba deposits Islamic Banks in Indonesia's period January 2011 – June 2015. The data used in this study are monthly data from January 2011 to June 2015. Technical sampling used in this research is purposive sampling, with a sample of 12 Islamic Banks recorded in data from Bank Indonesia. This study uses a computer program SPSS version 20.0 and Microsoft Excel 2007. The result in this research showed that Return On Asset (ROA) and Capital Adequacy Ratio (CAR) partially have significant effect on the level of profit sharing mudharaba deposits While the partial BOPO haven’t significant effect of the level of profit sharing mudharaba deposits Simultaneously, Return On Asset (ROA), Capital Adequacy Ratio (CAR) and BOPO had significant effect on the level of profit sharing mudharaba deposits The results also show that variable Return On Asset (ROA) the most dominant on the level of profit sharing mudharaba deposits with the value β of -0,273, and a significance value smaller than 0,05 (0,000 0, 05).